2015
DOI: 10.1002/bjs.9874
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of prevention of seroma formation after mastectomy by local methylprednisolone injection

Abstract: Methylprednisolone administered into the wound cavity on the first day after M + SLNB exerted a highly significant preventive effect against seroma formation during the next 30 days. This effect was not seen in the M + ALND group. Future studies may clarify whether higher or repeated methylprednisolone doses increase the efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
21
0
2
Order By: Relevance
“…This observational study was a part of a double-blind randomized placebo-controlled intervention study described in detail previously [15, 16]. Briefly, the original study (EudraCT number 2009-016650-40) analyzed the effect on seroma formation after mastectomy of a single dose of 80 mg of steroids into the mastectomy cavity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observational study was a part of a double-blind randomized placebo-controlled intervention study described in detail previously [15, 16]. Briefly, the original study (EudraCT number 2009-016650-40) analyzed the effect on seroma formation after mastectomy of a single dose of 80 mg of steroids into the mastectomy cavity.…”
Section: Methodsmentioning
confidence: 99%
“…Local administration of the steroid triamcinolone into the wound cavity after autologous latissimus dorsi breast reconstruction has been shown to reduce seroma formation [13], whereas a single intravenous bolus of steroids (methylprednisolone) before mastectomy exerted no effect [14]. Steroid administration into the wound cavity on the first day after mastectomy with sentinel lymph node biopsy exerted a significant preventive effect against seroma formation during the next 30 days, while no effect was observed after mastectomy with axillary lymph node dissection [15].…”
Section: Introductionmentioning
confidence: 99%
“…Seroma formation and its subsequent complications still the main postoperative problems after mastectomy or modified radical mastectomy, proving that wound drainage is inadequate in combating seroma. 12,13 The most important clue aiming to decrease seroma formation seems to be the closure of the dead space. However, the techniques used to accomplish this goal are subject of much controversy and debate.…”
Section: Discussionmentioning
confidence: 99%
“…Seroma formation is most likely the result of the inflammatory response due to wound healing. Comparison of drain fluid to plasma ratios with known lymph to plasma values for biochemical parameters showed that this fluid is compositionally different from lymph, but is similar to inflammatory exudates [2]. In the seroma fluid several factors have been detected that support this assumption.…”
Section: Introductionmentioning
confidence: 89%